1979
DOI: 10.1007/bf00447377
|View full text |Cite
|
Sign up to set email alerts
|

A case of biotin-responsive 3-methylcrotonylglycin- and 3-hydroxyisovaleric aciduria

Abstract: During selective screening for organic acidurias, a 10-week-old girl with muscular hypotonia and recurrent fits was shown to be excreting 3-methylcrotonylglycin and 3-hydroxyisovaleric acid. Besides these metabolites of leucine the presence of small but pathological amounts of propionic and methylcitric acids were demonstrable in her urine, pointing to a defect in the metabolism of biotin. On treatment with biotin (2 x 5 mg/day) the convulsions stopped at once, her clinical condition improved gradually, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Seizures have been described as generalized (Lehnert et al, 1979; Leonard et al, 1981; Thoene et al, 1981): grand mal, myoclonic and clonic (also reported in two siblings of a propositus) (Cowan et al, 1979), tonic (Sweetman et al, 1982), and usually myoclonic . But details of EEGs and samples have not been published.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Seizures have been described as generalized (Lehnert et al, 1979; Leonard et al, 1981; Thoene et al, 1981): grand mal, myoclonic and clonic (also reported in two siblings of a propositus) (Cowan et al, 1979), tonic (Sweetman et al, 1982), and usually myoclonic . But details of EEGs and samples have not been published.…”
Section: Discussionmentioning
confidence: 97%
“…Seizures have been reported as a prominent clinical feature in two of five HCSD cases (Wolf et al, 1981;Narisawa et al, 1982) and in 15 of 28 BD cases (Lehnert et al, 1979;Munnich et al, 1980;1981~;19816; Leonard et al, 1981; Thoene et al, 1981 ;Sherwood et al, 1982;Sweetman et al, 1982;Pocecco et al, 1983;Wolf et al, 19836;Diamantopoulos et al, 1984;Di Rocco et al, 1984;Fois et al, 1986;Low et al, 1986). Seizures have also been reported in an exceptional case of adult-onset form (Bressman et al, 1986) and in acquired biotin deficiency (Kien et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another patient presenting at a later age with intermittent acidosis has been shown to have low activities of the three carboxylases in fibroblasts cultured with low concentrations of biotin and marked increases in the activities when grown in medium with high concentrations of biotin (Bartlett et al, 1980). Another infant with a similar pattern of metabolite excretions, seizures, hypotonia, and seborrhoeic dermatitis also responded to treatment with biotin (Lehnert et al, 1979).…”
mentioning
confidence: 99%
“…Additionally, KIC is converted to isovaleryl-CoA and, through a number of reactions, is converted to HMB [3,4]. In conditions such as type II diabetes [5], biotin deficiency [6], isovaleric acidemia [7], β-methylcrotonyl-CoA carboxylase deficiency [8], and ketoacidosis [9], HMB accumulates in the urine due to altered leucine metabolism and as such is used as a marker for these conditions.…”
Section: Introductionmentioning
confidence: 99%